DERE SEBAGAI VARIASI BAHASA REMAJA - Sundawati Tisnasari (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Symptoms of language variation is part of language development even fragments of language problems. The development of language becomes a manifestation of the diversity of languages ??derived from human initiative copyright. It berdasaran result of incubation which is expressed in the realm of language creativity. This research study, that variation of the language with the addition dere form in the Indonesian vocabulary used by a group. The data source of this research is an oral narrative teenage secondary school (SMP) that is collected through recording technique. The use of language variation is used in a state of non-formal school environment. The symptoms of the changes found that the addition of the letter at the beginning of the word and the removal of the letters at the end of the word, like pergi --> dereper, Istirahat --> dereis, saya --> daresay, kau --> derekau, mau --> deremau. Variations of this language is a bit of linguistic phenomena are expected to contribute to the understanding of Indonesian society.